2019
DOI: 10.7554/elife.49226
|View full text |Cite
|
Sign up to set email alerts
|

Taste bud formation depends on taste nerves

Abstract: It has been known for more than a century that, in adult vertebrates, the maintenance of taste buds depends on their afferent nerves. However, the initial formation of taste buds is proposed to be nerve-independent in amphibians, and evidence to the contrary in mammals has been endlessly debated, mostly due to indirect and incomplete means to impede innervation during the protracted perinatal period of taste bud differentiation. Here, by genetically ablating, in mice, all somatic (i.e. touch) or visceral (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the geniculate ganglia, Phox2a/b-expressing neurons also play an indirect role in the migration and aggregation of parasympathetic precursors through the facial nerve, and in the guidance of visceral motor neurons projections (Coppola et al, 2010b). The trophic support provided by geniculate ganglia neurons innervation is also required for the formation of the taste buds (Fan et al, 2019). Similarly, visceral sensory and motor fibers constituting the vagus nerve, via their guidance role in the migration of Schwann cell precursors, contribute to the development of the ENS around the esophagus and the stomach (Espinosa-Medina et al, 2017).…”
Section: Phox2 Factors Are Essential Regulators Of the Entire Visceramentioning
confidence: 99%
“…In the geniculate ganglia, Phox2a/b-expressing neurons also play an indirect role in the migration and aggregation of parasympathetic precursors through the facial nerve, and in the guidance of visceral motor neurons projections (Coppola et al, 2010b). The trophic support provided by geniculate ganglia neurons innervation is also required for the formation of the taste buds (Fan et al, 2019). Similarly, visceral sensory and motor fibers constituting the vagus nerve, via their guidance role in the migration of Schwann cell precursors, contribute to the development of the ENS around the esophagus and the stomach (Espinosa-Medina et al, 2017).…”
Section: Phox2 Factors Are Essential Regulators Of the Entire Visceramentioning
confidence: 99%
“…We observed that the neuronal components in the stromal core were marked by ETB, an enteric nervous system marker, as well as PGP9.5 ( Figures 1D-F). In addition to this finding, Neurogenin2 was expressed in the underlying mesenchyme ( Supplementary Figures S1J-K), which marks neuroblasts (Fode et al, 1998;Okubo and Takada, 2015;Fan et al, 2019). Shh supposed to involve in stromal core formation via the regulation of neuroblasts-and NCCs-derived cell.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, nerve fibers in the underlying mesenchyme of CVP were stained by PGP9.5 according to our results. The population of neuroblasts was further confirmed by expression of Neurogenin-2, an essential transcription factor for neuronal development in the glossopharyngeal nerve (Fode et al, 1998;Harlow and Barlow, 2007;Okubo and Takada, 2015;Fan et al, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…Metallothionein-3 has been referred to as an inhibitor of neurite formation in developing neurons and postinjury regenerative neurite sprouting [ 187 ]. It has been suggested that the formation and development of taste buds and salivary glands depend on afferent nerves and sensory neurite growth [ 188 ]. If the expression of metallothionein-3 is upregulated by SARS-CoV-2 infection, the concentration change of cellular metallothionein-3 may affect taste buds and salivary glands to impair their gustatory and secretory functions.…”
Section: Discussionmentioning
confidence: 99%